Peningkatan Literasi Manajemen Filantropi Modern berbasis ZISWAF untuk Pemberdayaan Umat di Dompet Dhuafa Riau - Muhammad Iqbal; Lita Arfah; Dian Martha Darman; Marro’aini Marro’aini; Nur Sakinah (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2026)
This community service activity aims to improve literacy in modern philanthropic management based on zakat, infaq, alms, and waqf (ZISWAF) to support community empowerment at Dompet Dhuafa Riau. The main problem faced by the partner institution is the low level of public understanding regarding modern, professional, transparent, and productive economic-based Islamic philanthropic management. The implementation method used an educational and participatory approach through socialization, interactive discussions, and mentoring activities for participants. The materials presented included the concept of modern Islamic philanthropy, ZISWAF governance, digitalization of Islamic social fund management, and strategies for community economic empowerment through productive zakat. The results of the activity showed an increase in participants’ understanding of modern ZISWAF management and the importance of utilizing Islamic social funds productively. In addition, participants also gained a better understanding of transparency, accountability, and the use of digital technology in Islamic philanthropic management. This activity is expected to support the optimization of sustainable community economic empowerment programs through more effective and professional ZISWAF management